2019
DOI: 10.1038/s41431-019-0503-5
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ perspectives on the post-mortem use of genetic and health-related data for research: a systematic review

Abstract: The majority of biobank policies and consent forms do not address post-mortem use of data for medical research, thus causing uncertainty after research participants' death. This systematic review identifies studies examining stakeholders' perspectives on this issue. We conducted a search in MEDLINE, CINAHL, EMBASE and Web of Science. Findings were categorised in two themes: (1) views on the use of data for medical research after participants' death, and (2) perspectives regarding the post-mortem return of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…Thus, in the ARREST study no consent is asked from next-of-kin. While some respondents disagreed with this policy, others said data should be used without consent, for reasons similar to those mentioned by interview participants in other disease areas [ 86 ]. Interviewed next-of-kin seemed more uncomfortable with the idea of post-mortem data use than patients themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the ARREST study no consent is asked from next-of-kin. While some respondents disagreed with this policy, others said data should be used without consent, for reasons similar to those mentioned by interview participants in other disease areas [ 86 ]. Interviewed next-of-kin seemed more uncomfortable with the idea of post-mortem data use than patients themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with a previous study on the preference on information of incidental findings in genetic research [ 19 ]. A systematic review showed a high proportion of research participants who agreed on further use of genetic samples after the participant’s death [ 20 ]. There is still a minority who does not want to be informed of incidental findings or disagrees with use after death.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological researches based on post-mortem samples provide accessibility to all types of human tissues, which offer better understanding of the disease 1 . Currently, a research autopsy is commonly used, since it allows to expand the knowledge about the complex biology of cancer and the mechanism of metastasis formation 1 , thus there is a wide acceptance of donors’ relatives for the use of post-mortem samples for medical research 2 . These tissues are also extensively used in both clinical and forensic analyses, particularly in the case of toxicological tests 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%